2020
DOI: 10.1039/d0sc02520h
|View full text |Cite
|
Sign up to set email alerts
|

Au3-to-Ag3coordinate-covalent bonding and other supramolecular interactions with covalent bonding strength

Abstract: An efficient strategy for designing charge-transfer complexes using cyclic trinuclear complexes (CTCs) is described herein. Due to opposite quadrupolar electrostatic contributions from metal ions and ligand substituents, [Au(µ-Pz-(i-C3H7)2)]3.[Ag(µ-Tz-(n-C3F7)2)]3 has been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…S29–S33†). 8,18,50,51 A recent report revealed that for metal–metal bonds of metals with filled d-orbitals, the charge-shift character increases as the covalency decreases. 52 The electrostatic interactions lead to contributions of about 50% to the attraction energies in the EDA results, corresponding to the remarkable charge-shift character of the later transition metals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S29–S33†). 8,18,50,51 A recent report revealed that for metal–metal bonds of metals with filled d-orbitals, the charge-shift character increases as the covalency decreases. 52 The electrostatic interactions lead to contributions of about 50% to the attraction energies in the EDA results, corresponding to the remarkable charge-shift character of the later transition metals.…”
Section: Resultsmentioning
confidence: 99%
“…metal–metal interaction) in fields spanning from oligomeric metal complexes to atomically precise metal NCs remains a Sisyphus task by means of multiple descriptions in different narratives. 1,2,8–18…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the elongation of in-plane Li–O bonds (by the average values of 0.195%) is almost in the same magnitude with the out-of-plane cousins (by 0.210%) (Table S2), indicating that the interlayer and intralayer Li–O bonds have nearly the same bond strength. Moreover, bond energy is an explicit indicator of bond strength, , and the first-principles calculation revealed that the bond energy of the intralayer Li–O bond (average value of 1.2021 eV) is almost the same with the interlayer cousins (1.2022 eV) (Table S4). This demonstrates that the 2D NTE behavior can occur in the structure with similar in-plane and out-of-plane interaction.…”
Section: Resultsmentioning
confidence: 99%
“…If resources are still a constraint, Ag­(I) may be used instead of Au­(I) products, which do not require the synthesis of a starting material (AgNO 3 , AgBF 4 , and multiple other silver salts are commercially available and are soluble in many organic solvents). The Spring 2022 rendering of the same lab is currently examining Au–Cu, Au–Ag, and Cu–Ag mixed-metal products toward possible formation of a bona fide polar-covalent M–M′ bond following recent discoveries of such bonds. …”
Section: Lessons For Use At Other Institutionsmentioning
confidence: 99%